RELATIONSHIP BETWEEN WEIGHT, HEIGHT AND MOTOR COORDINATION IN CHILDREN OF A FOOTBALL (Fiep Bulletin - online, 2019)
This study aimed to verify the relationship between height, body mass index (BMI) and motor coordination of childrenin a soccer school. The sample consisted of schoolchildren aged 5 to 12 years, totaling 45 children in a population of 53. Theanthropometric measurements to measure height and BMI were based on the PROESP Manual and the KTK test battery,proposing to measure the capacity of motor coordination. The statistical treatment included the maximum, minimum, mean andstandard deviation calculations. For normality we used the Shapiro-Wilk test and the equality of variants, the test f for twovariants, relevance for the variances between height and BMI (F = 15.91). Correlation was analyzed by Pearson's correlationbetween height, BMI and motor coordination, observing only a significant correlation between height and BMI (r = 0.75, p = 1.21, n= 45). And Student's t-test, to verify possible differences between the same variants. According to the results, there was asignificant difference in level of p